The Effect of Tonsillectomy and Adenoidectomy on Isolated Sleep Associated Hypoventilation in Children. (2nd September 2020) - Saadeh, Charles; Ulualp, Seckin O.
Abstract : Objective: Sleep associated hypoventilation (SAH) is diagnosed when more than 25% of total sleep time (%TST) is spent with end tidal carbon dioxide (EtCO2 ) > 50 mmHg. SAH in children occurs as a single entity or combined with obstructive sleep apnea. Outcomes of surgical treatment for isolated SAH in children have not been reported. Methods: The medical charts of children who were diagnosed with isolated SAH and did not have OSA at a tertiary children's hospital between January 2013 and December 2019 were reviewed. Data collection included information on history and physical examination, past medical history, polysomnography (PSG) findings, and surgical management. Results: Seventeen children (10 male, 7 female, age range: 3–14 years) were diagnosed with isolated SAH. Comorbid conditions included asthma in four children, Down syndrome in one, and seizure in two. Eight children were normal weight, four were overweight, and five were obese. Children did not have obstructive or central sleep apnea. Three children (18%) had persistent SAH as documented by PSG. All normal weight children had resolution of SAH whereas two obese children and one overweight child had residual SAH. %TST with CO2 > 50 mmHg after upper airway surgery (3.4% ± 1.6%) was significantly less than that of before TA (59.1% ± 5.5%) ( P < .001). Conclusions: The majority of children with isolated SAH had normalization of hypercapnia after TA. Further studies in larger groups of children are needed to identify the risk factors for residual isolated SAH after TA. Level of Evidence: 4 Laryngoscope, 131:E1380–E1382, 2021